Eksplorasi Pengalaman Tim Kesehatan Stunting di Puskesmas dalam Pencegahan dan Penatalaksanaan Stunting pada Anak di Jayapura Papua - Hotnida Erlin Situmorang; Eva Sinaga (Universitas Malahayati Lampung, 2022)
ABSTRACT Stunting in children is one of the nutritional concerns of toddlers worldwide, including Indonesia. Stunting is a condition in which children under five fail to flourish as a result of chronic malnutrition, particularly in the first 1000 days of life (HPK). The quality of appropriate nutritional intake from the time the fetus is in the womb until the age of two years, or termed the first 1000 days of life, is one of the crucial variables in the production of human resources. The aim of the study was to explore the experiences of stunting team health workers at the community health center Jayapura Papua regarding the prevention and management of stunting in children. This research employed a descriptive qualitative method and data analysed based on thematic analysis. The study's findings revealed four main themes namely determining causes, difficulties encountered, teamwork, and expectations. The study concluded that the handling of stunting and programs handed down from the central government have been quite successful, but there needs to be an increase in cross-sectoral cooperation, involving religious leaders and traditional leaders to embrace the community, particularly stunting risk groups, as well as the need to improve the health team's skills through training regarding early stunting detection and management Keywords: Health Team, Experience, Stunting, Handling, Prevention ABSTRAK Stunting pada anak masih merupakan salah satu masalah gizi yang dialami oleh balita dunia hingga saat ini termasuk di Indonesia. Stunting merupakan kondisi gagal tumbuh pada anak balita akibat kekurangan gizi kronis terutama dalam 1000 Hari Pertama Kehidupan (HPK). Salah satu faktor penting dalam pembentukan sumber daya manusia adalah kualitas asupan gizi yang tercukupi sejak janin dalam kandungan hingga berusia 2 tahun atau disebut 1000 HPK. Penelitian ini bertujuan untuk mengeksplorasi pengalaman petugas kesehatan tim stunting di Puskesmas tentang pencegahan dan penatalaksanaan stunting pada anak. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan analisa data menggunakan tematik analisis. Hasil penelitian ini mendapatkan empat tema yaitu faktor determinan, tantangan yang dihadapi, kerja sama dan harapan. Kesimpulan dari penelitian ini adalah penanganan stunting dan program yang diturunkan dari pemerintah pusat sudah berjalan cukup baik, namun perlu adanya peningkatan kerja sama lintas sektoral,melibatkan tokok agama, tokoh adat untuk merangkul masyarakat terutama kelompok resiko stunting, serta perlunya peningkatan kemampuan tim kesehatan melalui pelatihan terkait deteksi dini stunting dan penanganan stunting. Kata Kunci: Tim Kesehatan, Pengalaman, Stunting, Penanganan, Pencegahan